Vulvar Cavernous Hemangioma: Case Report - Cüneyt Eftal Taner; İlkan Kayar; Aslı İris; Demet Aydoğan Kırmızı; Yasemin Göklü; Rıfat Göklü; Duygu Ayaz (Medical Network, 2016)
Vascular tumors of the female genitalia are unusual. Hemangiomas are benign tumors of the blood vessels. Usually they are asymptomatic and may be quite small. Histologically they are characterized by the endothelial cells and varying amount of supporting tissue. In this study a reproductive age woman who had symptomatic vulvar cavernous hemangioma is discussed.